Getting real in the language classroom: developing Japanese students' communicative competence with authentic materials - Gilmore, Alexander (2008)
The research described in this thesis reports on a 10-month quantitative/qualitative classroom-based study, carried out at a Japanese university, investigating the potential of authentic materials to develop learners’ communicative competence. It was hypothesised that the ‘richer’ input provided by authentic materials, combined with appropriate awareness-raising activities, would be better able to develop a range of communicative competencies in learners (linguistic, pragmalinguistic, sociopragmatic, strategic and discourse competences).